DESENVOLVIMENTO DE UM GEL COM CARREADOR LIPÍDICO NANOESTRUTURADO COM QUERCETINA, ANÁLISE DE SUA INTERAÇÃO COM ULTRASSOM TERAPÊUTICO E EFEITOS DA SONOFORESE EM LESÃO MUSCULAR DE RATOS - Moraes, Jefferson Potiguara de (2022)
Musculoskeletal injuries are common in living beings and occur due to direct trauma or indirect injuries. These induce a transient state of oxidative stress (OE), which occurs due to an excessive production of reactive oxygen and nitrogen species (RONS) and having an insufficient antioxidant capacity stimulates the inflammatory process. The use of exogenous antioxidants has been proposed as a therapeutic method to attenuate the secondary damage of these lesions and favor more myoregeneration. In this context, quercetin has been studied as a way to reduce OS, as it has antioxidant and anti-inflammatory properties. However, due to its low bioavailability, malabsorption due to its poor aqueous solubility, structural instability and extensive first-pass metabolism make its use as a therapeutic agent difficult. One solution is to use nanotechnology and incorporate quercetin into nanostructured lipid carriers (NCL) in gels for topical use, as it will provide quercetin with better physical stability and may favor passage through the stratum corneum. Therapeutic ultrasound (TUS), through phonophoresis, is a resource also used to facilitate the transport and distribution of drugs or therapeutic compounds through the skin. In this sense, studying this interaction is of paramount importance. The aim of this study was: (1) to produce, characterize and evaluate the stability of this nanostructured lipid carrier loaded with quercetin incorporated into a gel (NLC-Q gel) (2) to evaluate the effects of this structure (NLC-Q gel) at different pulsed ultrasound therapeutic (PUT)intensities, and also (3) to study the sonophoresis effects (PUT with NLC-Q gel) on OS parameters, inflammatory response and histological changes in rat gastrocnemius muscle contusion injury. The quercetin-loaded nanostructured lipid carriers (NLC-Q) were produced by the high shear rate, and characterization and stability studies were carried out for 30 days and these were introduced to a gel, which was evaluated for 60 days at three different temperatures. 25°C, 5°C and 40°C. NLC-Q and NLC-Q gel showed good stability at room temperature 25 ºC throughout the study. After the NLC-Q gel was submitted to the action of PUT (1 MHz, for 5min, 20% duty cycle) at intensities of 0.1, 0.2, 0.4 and 0.6 W/cm2SATA (spatial averaged–temporal intensity) with the objective of evaluating changes in pH, temperature, size, polydispersity index (PI) and quercetin concentrations contained in the NLC-Q gel. It was observed that PUT interferes with NLC-Q contained in gel, and higher intensities can impair the delivery of the transdermal active ingredient. Subsequently, the NLC-Q gel was applied (5 interventions every 12 hours) with PUT (1 MHz, for 5min, 20% duty cycle and intensity of 0.1W/cm2SATA) on a contusion injury in the gastrocnemius muscle of rats. Wistar. The results showed that Sonophoresis reduced oxidative stress and accelerated tissue repair of muscle injury evaluated 96h after injury. These studies demonstrate the development, characterization, stability and application of NLC-Q gel through sonophoresis, in muscle injury in rats. The results suggest that this new therapeutic approach in the treatment of musculoskeletal injuries presents relevant results and deserves to be clinically tested.